THE CONCEPT OF SUSTAINABLE DEVELOPMENT IN ECONOMIC RESEARCH: QUANTITATIVE AND LEXICO-SEMANTIC DIMENSIONS - YANOVSKA, Viktoriia; PARFENTIEVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
On the basis of the conducted research, it was established that in Ukraine for the period of 2007–2021, 132 PhD theses, 110 doctoral dissertations, and 14 PhD theses were defended in the field of economic sciences on the topic of sustainable development. Active interest in the issue of sustainability began to manifest itself in the early 2000s. Up to and including 2014, the number of dissertations grew steadily, but at different speeds, 2016 was the year of the minimum degree of academic activity, after which the growth in the number of defenses resumed, which was largely due to the actualization of issues at the state level, starting from 2020, the positive dynamics were strengthened by the process of defenses for obtaining the degree of Doctor of Philosophy. Focusing on the topics of dissertations allows us to assert the comprehensive penetration of the ideology of sustainable development into the space of scientific research in the field of economic sciences. The distribution of works by the frequency of sectoral research in the field of sustainable development economics shows that the lion’s share of dissertations was prepared on the economy as a whole, while active scientific work was carried out on the issues of sustainable development of the agro-industrial complex, industry, and to a lesser extent, transport and tourism. The analysis of the topics through the prism of the conceptual field made it possible to form a stable grouping of typologically and semantically homogeneous and hierarchically ordered concepts, divided into twelve lexical-semantic subclasses, partially combined into three groups of categories and presented as a structured system consisting of a core and a periphery. The analysis of the dynamics of defended dissertations, the examination of the distribution of dissertations by majors and scientific degrees, the study of the frequency of mentioning the branches of economics in the topics and, accordingly, the degree of branch orientation of the works made it possible to quantitatively assess the scope and identify trends in scientific research, the formation of a conceptual field based on the results of cognitive generalizations and with the help of mapping made it possible to verbalize qualitative parameters, demonstrate the content, variability and lexical-semantic interconnection of scientific research.